Comparison of combustion emissions between manual and machine set methods to reduce carbon monoxide (CO) in briquette manufacturing - Ega Nugraha Firdaus; Ayu Wulandari; Silvia Fauzia Marreta; Farah Aqila Mahfudzah Nasution (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Renewable energy from biomass is one solution to reduce dependence on fossil fuels and the impact of carbon emissions. One form of renewable energy from biomass is briquettes. This study aims to analyze the effectiveness of using modern technology in the form of a briquette production machine set consisting of a grinder, extruder, and burner integrated with a wet scrubber innovation to reduce carbon monoxide (CO) emissions from rice husk combustion in the burner machine compared to the manual method. Methods: The research process was carried out through the stages of needs identification, CAD (Computer Aided Design)-based machine design, prototype production, and briquette performance testing using a Non-Dispersive Infrared (NDIR) analyzer. Findings: The test results showed that briquettes produced using the manual method had a higher density of 0.8 g/cm³ and produced an average CO emission of 220 ppm. These findings prove that mechanizing the process improves the physical quality of the briquettes while reducing CO emissions by around 39%. The integration of wet scrubber technology proved to be effective in absorbing additional exhaust gases and strengthening the environmentally friendly aspects of the combustion process. Conclusion: The conclusion of this study confirms that the use of integrated machinery not only improves briquette quality and energy efficiency, but also makes a significant contribution to carbon emission control efforts at the local level. Novelty/Originality of this Article: The novelty of this study lies in its comprehensive analysis comparing manual and mechanized methods using burner machines with integrated wet scrubbers in the context of rice husk briquette production.